Effects analysis on soot oxidation performance in the diesel particulate filter based on synergetic passive-active composite regeneration methods. (23rd November 2022) - Zhong, Chao; Liang, Jingwei; Zhu, Yun; Zuo, Hongyan; Wang, Shaoli; Chen, Bo; Wu, Xin; Wu, Chenxi
Graphical abstract: Highlights: A coupled model of DPF passive and active regeneration is established. Control regime transition of DPF regeneration mechanisms is investigated. Key parameters affecting soot oxidation mechanisms are summarized. Abstract: Diesel particulate filters (DPFs) are standard components to control particulate emissions from diesel engine. Different DPF regeneration mechanisms, including passive regeneration and active regeneration, affect the performance of itself and downstream post-processing equipment. In order to study soot oxidation mechanism in DPF, DPF passive-active coupled regeneration model is established, and its kinetic parameters are verified. Active-passive regeneration balance point temperature (APR-BPT), passive regeneration control upper bound temperature (PR-UBT) and active regeneration control lower bound temperature (AR-LBT) are defined to study-three control regimes affected by two soot oxidation mechanisms. Additionally, the effect analysis of key parameters on APR-BPT, PR-UBT and AR-LBT is conducted to reveal the regeneration regime and the regeneration temperature boundary. The research on the soot combustion mechanisms under the synergetic passive-active composite regeneration of the DPF will provide a theoretical basis for DPF regeneration and its control.